PENGARUH BENTUK KOMUNIKASI KELUARGA YANG DILAKUKAN ORANG TUA TERHADAP ANAK DALAM PEMBELIAN PRODUK MAINAN DI KOTA SURABAYA - Andry Herawati, Fedianty Augustinah (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2010)
Children play an important role in deciding goods procurement within a family. Although children are influencers, they canchange or determine family list of errands. The decisions children make are, to a certain extent, shaped by how parents communicate with their children. Socialization process through family communication is very important for the development process of a child as a consumer. The family communication consists of socio-orientation and concept-orientation. Socioorientation is the communication where parents monitor and control the children?s attitudes and learning as consumers. Meanwhile, concept-orientation is the communication in which parents support their children?s ability to make decision over purchasing. The type of communication adopted by parents affects children over purchasing decision making.